Antioxidant Therapy in Pancreatitis - Lourdes Swentek; Dean Chung; Hirohito Ichii (MDPI AG, 2021)
Pancreatitis is pathologic inflammation of the pancreas characterized by acinar cell destruction and oxidative stress. Repeated pancreatic insults can result in the development of chronic pancreatitis, characterized by irreversible fibrosis of the pancreas and many secondary sequelae, ultimately leading to the loss of this important organ. We review acute pancreatitis, chronic pancreatitis, and pancreatitis-related complications. We take a close look at the pathophysiology with a focus on oxidative stress and how it contributes to the complications of the disease. We also take a deep dive into the evolution and current status of advanced therapies for management including dietary modification, antioxidant supplementation, and nuclear factor erythroid-2-related factor 2-Kelch-like ECH-associated protein 1(Nrf2-keap1) pathway activation. In addition, we discuss the surgeries aimed at managing pain and preventing further endocrine dysfunction, such as total pancreatectomy with islet auto-transplantation.